Adoption of Dairy Farmers Regarding Breeding and Management Practices of Buffalo Husbandry (Indian Journal of Extension Education, 2011)
The study was conducted on 240 buffalo owners selected from eight villages of Haryana state to find out the adoption of buffalo owners regarding breeding and management practices of buffalo husbandry. The study reveals that respondents of all categories possessed medium level of adoption about breeding and management practices ranging from 45.00 to 57.00 percent followed by poor and highest adoption level respectively. The higher adoption was recorded in AI services, watching on oestrous cycle and importance of ventilated animal sheds by the respondents of each category. While they had never taken care of artificial nurturing of newly born calfs. Results also indicated that all the independent variables were having highly significant and positive relationship except age which has negative significant correlation with extent of adoption of breeding and management practices.